2011
DOI: 10.1002/uog.8968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uterine anomalies and their impact on early pregnancy in women conceiving after assisted reproduction treatment

Abstract: Objective To estimate the prevalence of congenital uterine anomalies in subfertile women and to evaluate their influence on early pregnancy following assisted reproduction treatment (ART). Methods (n = 164 (11.8%)) followed by septate (n = 7 (0.5%)), unicornuate (n = 6 (0.4%)), subseptate (n = 5 (0.4%)), bicornuate (n = 1 (0.1%)) and T-shaped uteri (n = 1 (0.1%)). A total of 440 subjects who underwent ART were followed up. The pregnancy rates in women with arcuate uteri (36/66 (54.5%)) and major uterine anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 15 publications
2
69
1
1
Order By: Relevance
“…MR G uterin anomalilerin tanısını koymada sensitivitesi ve spesifisitesi oldukça yüksek altın standart bir yöntemdir. 7,8 Kara ve ark., çalışmalarında, bikornuat uterusun tekrarlayan gebelik kaybına yol açabileceğini ve gebeliğin sonlandırılması işlemi sırasında uterin perforasyon riskinin arttığını belirtmişlerdir. Ayrıca, bikornuat uterusu olan bir olguda gebelik sonlandırması için medikal abortus yöntemlerinin tercih edilmesini önermişlerdir.…”
Section: Discussionunclassified
“…MR G uterin anomalilerin tanısını koymada sensitivitesi ve spesifisitesi oldukça yüksek altın standart bir yöntemdir. 7,8 Kara ve ark., çalışmalarında, bikornuat uterusun tekrarlayan gebelik kaybına yol açabileceğini ve gebeliğin sonlandırılması işlemi sırasında uterin perforasyon riskinin arttığını belirtmişlerdir. Ayrıca, bikornuat uterusu olan bir olguda gebelik sonlandırması için medikal abortus yöntemlerinin tercih edilmesini önermişlerdir.…”
Section: Discussionunclassified
“…Until 2000, the combined use of laparoscopy (LSK) and hysteroscopy (HSK) was considered the gold standard for diagnosis of mullerian duct anomalies, due to the capabilities to assess the external and internal contour, respectively ( Figure 2) [16][17][18][19][20]. Still, in many cases the two investigations are separately performed by different operators, and thus, the diagnosis accuracy may be influenced.…”
Section: Combined Laparoscopy and Hysterosalpingographymentioning
confidence: 99%
“…Congenital uterine anomalies are a result of abnormalities that occur along different stages of embryological development. [1][2][3] Agenesis of müllerian ducts, precursors to the cervix, the uterus, upper two-thirds of the vagina and the fallopian tubes, in the initial stages of development lead to unicornuate uterus. Failure or improper lateral fusion of the müllerian ducts can lead to formation of bicornuate or didelphic uteri.…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent study that used 3D ultrasound for diagnosis, reported that the rate of congenital uterine anomalies is 13.3% in the subfertile female population. 2 One of the few indications that this abnormality is present in a patient is that the miscarriage rate is higher in women with congenital uterine anomalies compared with healthy women. This condition is uncommonly diagnosed because of the different types of imaging used, which has been traditionally quite limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation